Cyclodiphosph(III)azane chemistry – ylides from the reaction of [(RNH)P-N(t-Bu)]2 [R = t-Bu, i-Pr] with dimethyl maleate and chiral ansa-type derivatives from reaction of [ClP-N(t-Bu)]2 with a substituted BINOL - Swamy, K.C. Kumara; Gangadhararao, G.; Srinivas, Venu; Kumar, N. N. Bhuvan; Balaraman, Ekambaram; Chakravarty, Manab (Inorganica Chimica Acta, 2011)
Use of a simple inorganic ring system with the cyclodiphosph(III)azane skeleton [e.g. [(RNH)P-N(t-Bu)]2 [R = t-Bu (7), i-Pr (8)] to probe some of the intermediates proposed in phosphine mediated organic reactions is highlighted. Thus the reaction of 7–8 with the allenylphosphine oxide Ph2P(O)C(Ph)double bond; length as m-dashCdouble bond; length as m-dashCH2 (9) affords the phosphinimines [(RNH)P(μ-N-t-Bu)2P(double bond; length as m-dashN-R)-C(double bond; length as m-dashCH2)CH(Ph)-P(O)Ph2] [R = t-Bu (10), i-Pr (11)], while a similar reaction of 7–8 with dimethyl maleate (or dimethyl fumarate) affords the ylides [(RNH)P(μ-N-t-Bu)2P(NH-R)double bond; length as m-dashC(CO2Me)-CH2(CO2Me) [R = t-Bu (18), i-Pr (19)]. The implication of such reactions on phosphine mediated organic transformations including Morita–Baylis–Hillman reaction is mentioned. In a rather rare type of situation, an unusually long phosphoryl (Pdouble bond; length as m-dashO) bond [1.538 (5) Å] as revealed the X-ray structure of {(R)-6,6′-(t-Bu)2-1,1′-(C10H5)2-2,2′-O2-}{P(O)(N-t-Bu)2-P(Se)} (27) is rationalized by means of crystallographic disorder in packing after comparing the data with that in the literature and {1,1′-(C10H6)2-2,2′-O2}{P(Se)(N-t-Bu)2-P(Se)} (29). X-ray structures of the new compounds 10–11, 18–19, 27 and 29 are discussed. Compound 10 crystallizes in the chiral space group Pca2(1) with (S)-chirality at the carbon center [–C(double bond; length as m-dashCH2)CH(Ph)-P] suggesting a case of spontaneous resolution through crystallization.

Easy access to alpha-aryl substituted gamma-ketophosphonates: lewis acid mediated reactions of 1,3-diketones with alpha-hydroxyphosphonates and tandem regioselective C-C bond cleavage - Pallikonda, Gangaram; Chakravarty, Manab; Sahoo, Manoj Kumar (Organic & Biomolecular Chemistry, 2014)
A range of alpha-aryl substituted gamma-ketophosphonates is synthesised by Lewis acid mediated reactions of 1,3-diketones and easily accessible, inexpensive benzylic alpha-hydroxyphosphonates in an operationally simple method under solvent-free conditions without exclusion of air/moisture. A regioselective C-C bond cleavage for 1,3-diketones in a tandem fashion has also been demonstrated. Synthesis of a gamma-ketophosphonate with phenol functionality at the a-position (structural analogue of raspberry ketone, a natural product) has also been presented.